PENINGKATAN LITERASI AWAL MELALUI FLASHCARD BERBASIS VEKTOR PADA SISWA KELAS I SD NEGERI KEDUNGJENAR - Alifia Adhila; Wildan Farih Kurniawan; Ahmad Teguh Purnawanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early reading and writing skills remain low, while prior studies emphasize media use without examining visual quality. This study aims to improve early literacy through vector-based flashcards designed with precise visual features to enhance letter recognition accuracy. The method employed was Classroom Action Research using the Kemmis and McTaggart model in two cycles involving 28 first-grade students. Data were collected through tests, observations, interviews, and documentation, then analyzed quantitatively and qualitatively. The results show an increase in the mean score from 69 to 85 and mastery from 68% to 93%, indicating improved recognition and representation of language symbols. These findings confirm that visual quality functions as a cognitive factor in early literacy learning effectiveness.